OTAK RASIONAL, OTAK EMOSIONAL, OTAK SPIRITUAL DALAM PENDIDIKAN ISLAM - liana, inggi desy; Suyadi, Suyadi (IAIN Bone, 2024)
The brain is the human control center, which gives humans the ability to think, move, breathe, and so on. Education is one way to hone brain abilities, the result of various brain performances such as rational, emotional and spiritual intelligence. So far the existing studies only discuss the results of brain work (intelligence) in Islamic education, whereas Scientific brain studies are still rarely explored by researchers. The aim of this research is to complement existing research, to determine the optimization of the rational, emotional and spiritual brain in Islamic education. This research uses qualitative methods with a library research approach. The results of this research discuss optimizing brain performance in Islamic education, because education is a process of training students' rational, emotional and spiritual abilities. Optimizing the brain will be easy if the basic basics of brain anatomy are recognized and understood, then analyzed, then stimulated